Stingless bee honey as a halalan tayyiban superfood: the beekeepers challenges - Amir, Adibah; Mat Jebah, Ahmad Suhairi; Ahmad, Mohd Yazid (2021)
This paper examines the beekeeping activities in Malaysia that covered urban type of beekeepers. In the post-pandemic situation currently, beekeeping had been showing great potential as a sustainable income generator as well as influencing biodiversity and ecosystem. Stingless bee honey has been gaining its reputation as superfood and been sought after following many scientific discoveries of its fantastic health and medicine benefits. This paper analyzes the challenges faced by beekeepers in producing sufficient supply of stingless bee honey for national and international market. This paper looks in detail at the golden potential to enhance and strengthen this super food to be marketed as a halalan toyyiban super food. The findings suggested the harmonization of roles and responsibilities between research institutes, agricultural sector, government agencies and farmers are the key factor to penetrate international market. It is also recognized that intensive marketing on promoting authentic stingless bee honey as a halalan toyyiban super food to our societies must be further increased and widespread.